إعادة الاعتبار للمتحف البلدي للكشاف (الكنيسة سابقا) بالجلفة - حميدي, فاطمة الزهراء (Laghouat : Université Amar Telidji - Département d'architecture, 2022)
Museum is an important means of communication because it is the most prominent places that having a specific character and stand for specific objectives.It is also considred an educational institution which aimed at maintaining the heritage of the peoples and their history,and to preserve the culture of the past for the new generations of the future .that's why we choose the Museum of scouts in el djelfa, which is a memorial and part of the history of the region. Though it has been built diring the colonial period, it has not received a great historical interest . Our study has been in re-consideration of this heritage through the Architectural study in order to establish a database as a starting point for any future intervention about this museum the , with diagnosis, we can determine the processes that must be made to promote and retrieve the value of this monument and make it a famous element in the city centre.